Correlated Perovskites as a New Platform for Super‐Broadband‐Tunable Photonics. Issue 41 (30th August 2016) - Li, Zhaoyi; Zhou, You; Qi, Hao; Pan, Qiwei; Zhang, Zhen; Shi, Norman Nan; Lu, Ming; Stein, Aaron; Li, Christopher Y.; Ramanathan, Shriram; Yu, Nanfang
Abstract : The electron‐doping‐induced phase transition of a prototypical perovskite SmNiO3 induces a large and non‐volatile optical refractive‐index change and has great potential for active‐photonic‐device applications. Strong optical modulation from the visible to the mid‐infrared is demonstrated using thin‐film SmNiO3 . Modulation of a narrow band of light is demonstrated using plasmonic metasurfaces integrated with SmNiO3 .